An ALMA survey of the SCUBA-2 Cosmology Legacy Survey UKIDSS/UDS Field: identifying candidate z∼4.5[CII] emitters - Cooke, E.A.; Smail, Ian; Swinbank, A.M.; Stach, S.M.; An, Fang Xia; Gullberg, B.; Almaini, O.; Simpson, C.J.; Wardlow, J.L.; Blain, A.W.; Chapman, S.C.; Chen, Chian-Chou; et al. (American Astronomical Society, 2018)
We report the results of a search for serendipitous [C ii] 157.74 μm emitters at z sime 4.4–4.7 using the Atacama Large Millimeter/submillimeter Array (ALMA). The search exploits the AS2UDS continuum survey, which covers ~50 arcmin2 of the sky toward 695 luminous (S 870 gsim 1 mJy) submillimeter galaxies (SMGs), selected from the SCUBA-2 Cosmology Legacy Survey 0.96 deg2 Ultra Deep Survey (UDS) field. We detect 10 candidate line emitters, with an expected false detection rate of 10%. All of these line emitters correspond to 870 μm continuum-detected sources in AS2UDS. The emission lines in two emitters appear to be high-J CO, but the remainder have multi-wavelength properties consistent with [C ii] from z sime 4.5 galaxies. Using our sample, we place a lower limit of $\gt 5× {10}^{-6}\,Mpc^{-3}$ on the space density of luminous (L IR sime 1013 ${L}_{\odot }$) SMGs at z = 4.40–4.66, suggesting $\geqslant 7$% of SMGs with ${S}_{870μ {\rm{m}}}\gtrsim 1$ mJy lie at 4 < z < 5. From stacking the high-resolution (~0farcs15 full-width half maximum) ALMA 870 μm imaging, we show that the [C ii] line emission is more extended than the continuum dust emission, with an average effective radius for the [C ii] of ${r}_{{\rm{e}}}={1.7}_{-0.2}^{+0.1}$ kpc, compared to r e = 1.0 ± 0.1 kpc for the continuum (rest-frame 160 μm). By fitting the far-infrared photometry for these galaxies from 100 to 870 μm, we show that SMGs at z ~ 4.5 have a median dust temperature of T d = 55 ± 4 K. This is systematically warmer than 870 μm selected SMGs at z sime 2, which typically have temperatures around 35 K. These z sime 4.5 SMGs display a steeper trend in the luminosity-temperature plane than z ≤ 2 SMGs. We discuss the implications of this result in terms of the selection biases of high-redshift starbursts in far-infrared/submillimeter surveys.